Development of an IoT-Based Occupancy Control System to Minimize the Spread of Covid-19 in Closed Environment - Alshahrani, Suhail S; Alokaily, Ahmad O (British Journal of Healthcare and Medical Research, 2022)
Due to the recent COVID-19 pandemic, there has been a continued need to control and monitor closed environment areas. Advances in technology and the Internet of Things (IoT) applications could play an important role in facilitating and automating the imposed regulations to limit the spread of airborne infections such as COVID-19. In this paper, a cost-effective automated IoT-based occupancy system to monitor and control visitor traffic in closed areas is proposed. The system was built based on commercially available microcontrollers instructing visitors to follow COVID-19 spread prevention measures. Prototype testing and validation show the system was able to provide real-time occupancy information and prevent entry to visitors with a fever. The system has the potential to be used in most critical areas where visitor numbers should be limited and controlled.